The accuracy of heparin-binding protein and interleukin-6 in predicting prognosis of severe pneumonia with sepsis patients - Wei, Zhiyong; YuSuPu, Maimaitijiang; Wang, Xiaoye; Meng, Yu; Zhang, Chunli; Xue, Xiaomeng; Cui, Yan; Xie, Keliang (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundEarly warning is critical for improving prognosis in patients with severe pneumonia-induced sepsis. Conventional biomarkers and the Sequential Organ Failure Assessment (SOFA) score have notable limitations in sensitivity, specificity, and timeliness. This study aimed to evaluate the prognostic value of serum heparin-binding protein (HBP) and interleukin-6 (IL-6), assess their correlation with clinical outcomes, and compare their predictive performance against traditional biomarkers and the SOFA score.MethodsA total of 171 patients with severe pneumonia complicated by sepsis were enrolled and stratified into survivor (n=96) and non-survivor (n=75) groups based on 28-day mortality. Baseline characteristics, including demographic data, comorbidities, and laboratory markers—HBP, IL-6, procalcitonin (PCT), C-reactive protein (CRP), lactate (Lac)—as well as SOFA scores, were collected upon admission. Multivariate logistic regression was performed to identify independent predictors of mortality. Predictive accuracy was assessed using receiver operating characteristic (ROC) curve analysis, with pairwise comparisons of area under the curve (AUC) conducted via DeLong’s test. Spearman’s rank correlation was used to evaluate the association between biomarker levels and organ dysfunction severity. Statistical significance was defined as P<0.05.ResultNon-survivors had significantly higher HBP, IL-6, PCT, CRP, Lac, and SOFA scores than survivors (all P<0.05). IL-6 was markedly elevated in blood culture-positive patients (P<0.05), suggesting value in detecting bloodstream infections. Multivariate analysis confirmed HBP (OR = 1.006, 95% CI:1.002–1.011), IL-6 (OR = 1.004, 95% CI:1.001–1.007), and SOFA score (OR = 1.026, 95% CI:1.145–1.484) as independent prognostic factors (all P<0.05). ROC analysis showed IL-6 had the highest AUC (0.80), followed by SOFA (0.78) and HBP (0.73), with no significant AUC differences between IL-6 and SOFA (P = 0.719) or HBP and CRP/PCT (both P>0.05). Optimal cut-offs were 55.90 ng/mL for HBP (sensitivity 82.7%, specificity 53.1%) and 32.62 pg/mL for IL-6 (sensitivity 77.3%, specificity 69.8%). HBP correlated strongest with SOFA (r=0.60, P<0.01).ConclusionSerum HBP and IL-6 have comparable predictive efficacy to SOFA score and are numerically superior to PCT, CRP, and Lac. IL-6 also aids early identification of bloodstream infections. However, their cut-offs are from a single-center cohort and require external validation; combined use with SOFA score is recommended clinically.